Diagnostic informativeness of markers of bone-tissue metabolism and bone resorption in cows with osteodystrophy - L. G. Slivinska; V. L. Fedorovych; A. R. Shcherbatyy; N. M. Fedorovych; B. V. Gutyj; V. V. Vlizlo; M. G. Lychuk; I. A. Maksymovych; H. O. Zinko (Regulatory Mechanisms in Biosystems, 2023)
Osteodystrophy is caused by polyetiological factors, the main being disturbance of metabolism of macroelements and D and A vitamins. The disease continues to impose great economic losses on animal husbandry, reduces cattle productivity, and hinders effective work in this sphere. To study the pathogenesis and early diagnostics of bovine osteodystrophy, we examined the markers of metabolism of the connective tissue: macro- and microelements, general glycosaminoglycans and their fractions, chondroitin sulfate, sialoglycoproteins, oxoproline, citric acid, and osteocalcin. In the cows with subclinical course of osteodystrophy, the content of total calcium was decreased by 18.9% and such of phosphorus by 5.7%. In 95% of the clinically ill animals, we diagnosed hypocalcemia, combined with hypophosphatemia, in 35.0% of the cows. In blood serum of the cows with subclinical course of osteodystrophy, we found decrease in the concentration of citric acid down to 157.7 ± 2.1 mmol/L, in the clinically ill – 146.8 ± 1.2 mmol/L and osteocalcin – to 1.12 ± 0.04 and 0.72 ± 0.04 ng/mL, respectively. We determined increases in concentrations of chondroitin sulfates, sialoglycoproteins, total glycosaminoglycans and their fractions: chondroitin-6-sulfate, chondroitine-4-sulfate, keratan- and heparin- and dermatan sulfates, and heparine. The most informative criteria for diagnostics of subclinical course of osteodystrophy were citric acid, total glycosaminoglycans and their first and third fractions, chondroitin sulfates and sialoglycoproteins, because they were above the physiological limits in 100% of the cows with subclinical course of the disease, whereas in the clinically healthy animals, osteocalcin decreased in 60 and 100% of the cases, respectively.